Impacts of κ- oligocarrageenan application on photosynthesis, nutrient uptake and bean yield of coffee (Coffea robusta) - Pham, Trung San; Chau, Minh Khanh; Huynh, Hoang Nhu Khanh; Truong, Anh Khoa; Nguyen, Hoang; Pham, Duc Thinh; Nguyen, Thanh-Danh (Penerbit Universiti Kebangsaan Malaysia, 2021)
κ-Oligocarrgeenan (OC) is well known as an effective and green plant growth promoter and elicitor. However, its effect on coffee plant has not been investigated so far. This study aimed to examine the impacts of OC on biophysical activity, vegetative growth and productivity of coffee plant (Coffea robusta). OC with average molecular weight (AMW) of 4.0 kDa was prepared by depolymerization of carrageenan using ascorbic acid. Field experiments were conducted by foliar spray four times per year at various OC concentrations (50, 100, 150, 200, and 250 ppm) for three years (2017-2019). The results showed that OC promoted growth of coffee plant in all tested concentrations, and an optimized concentration was found at 150 ppm which showed a significant increase compared to the control plant in total chlorophyll (24.79%), carotenoid (31.65%), uptakes of N (15.66%), P (15.81%), and K (22.25%) minerals in leaves, crop yield (19.80%) and bean size (13.10%). Therefore, OC is potentially promising to apply as a promoter to enhance yield of crops for sustainable coffee plantation.